Normal Dimensions of Lateral Femoral Condyle in Pakistani Population - Hidayat Ullah; Hidayat Ullah; Saeed Ahmad; Zia Ullah; Mehtab Ullah; Zahid Askar; Malik Javed Iqbal (ziauddin University, 2024)
Background: The medial condyle is wider and has a larger surface area for articulation than the lateral femoral condyle however anteroposteriorly lateral femoral condyle is larger. This study aimed to find normal dimensions of the lateral femoral condyle in the Pakistani population. Methods: This Cross-sectional descriptive study, was carried out from September 2023 to May 2024 in the Radiology department of Peshawar General Hospital, Peshawar with a sample size of 385. Non - probability convenience sampling technique was used. All healthy adults, with intact femurs with clear features were included and scanned through magnetic resonance imaging. Data analysis was done through SPSS version 22, descriptive analysis was done and association was assessed by applying independent sample t-test and ANOVA. P-value ≤ 0.05 is considered statistically significant. Results: About 54% (n=149) male participants and 60% (n=67) of females had right knee measurements, whereas 46% (n=125) males and 40% (n=44) females had measurements of their left knee. There was no significant relationship between gender and the measured side (p=0.169). Age and size of the lateral femoral condyle were shown to be significantly correlated (p=0.027). Males exhibited greater femoral condyle dimensions, notch widths, and heights compared to females (p<0.001). Furthermore, ANOVA showed statistically significant variations in parameters of lateral femoral condyle, notch width, and height with age (p<0.001). Conclusions: This study demonstrates that the femoral condyles parameters depend on several variables and differ by gender and region. Considering this study, accurate tunnel in lateral femoral condyle can be made for anterior cruciate ligament graft in ACL injury.